Safety and Efficacy of Rotigotine for Treating Parkinson's Disease: A Meta-Analysis of Randomised Controlled Trials - Fei Chen; Lingjing Jin; Zhiyu Nie (Frontiers Media S.A., 2017)
We aimed to comprehensively analyse the safety and efficiency of rotigotine for treating Parkinson's disease (PD). We conducted systematic literature searches of Cochrane library, PubMed and Embase databases up to April 2016, with 'Rotigotine', 'Parkinson Disease ' and 'Parkinson's disease' as key searching terms. Outcomes, including Unified Parkinson's Disease Rating Scale (UPDRS) Part III and Part II scores, 'off' time, adverse events (AEs), serious AEs and discontinuation because of AEs, were compared between rotigotine and placebo groups under a fixed or random effect model. For dichotomous and continuous data, risk ratio (RR) and weighted mean difference with their corresponding 95% confidence intervals (95% CIs) were taken as the effect sizes to calculate merged results. Twelve eligible studies were included. For patients with early or advanced PD, rotigotine could significantly improve UPDRS Part III and Part II scores (p < 0.001) and it had significantly higher incidence of AEs than the placebo (p < 0.001). Regarding discontinuation because of AEs, rotigotine showed a significant advantage over placebo in patients with early PD, whereas the overall result demonstrated no statistically significant difference between the groups. Rotigotine can improve daily living and motor ability of patients with PD, although it has higher incidence of AEs. Rotigotine might be more appropriate for patients with advanced PD than for those with early PD.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.